2017
DOI: 10.4257/oeco.2017.2101.06
|View full text |Cite
|
Sign up to set email alerts
|

ECOLOGICAL ASPECTS OF NEMATODE PARASITES OF Didelphis aurita (DIDELPHIMORPHIA, DIDELPHIDAE) IN URBAN-SYLVATIC HABITATS IN RIO DE JANEIRO, BRAZIL

Abstract: Despite the widespread occurrence and the great number of studies of the common opossum Didelphis aurita (Didelphimorphia, Didelphidae), there is a serious lack of information about helminth parasitism in these species. The synanthropic characteristic of these animals may influence their parasite fauna and the ecological parameters. We evaluated the abundance, intensity, prevalence and spatial aggregation of the most abundant nematodes of the large intestine and stomach, recovered from the common opossum D. au… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 15 publications
1
5
0
3
Order By: Relevance
“…This pattern is most common in species with a polygamous mating system (Poulin, 2007), but there is no information in the literature about the mating system of these species. Nonetheless, similar results were found by Antunes (2005), Castro et al (2017) and Costa-Neto et al (2019) for C. tentaculata.…”
Section: Discussionsupporting
confidence: 89%
“…This pattern is most common in species with a polygamous mating system (Poulin, 2007), but there is no information in the literature about the mating system of these species. Nonetheless, similar results were found by Antunes (2005), Castro et al (2017) and Costa-Neto et al (2019) for C. tentaculata.…”
Section: Discussionsupporting
confidence: 89%
“…Parasites have important ecological roles in ecosystems because they affect the fitness of their hosts, promote changes in their physiology and population dynamics, regulate host populations, mediate competition and predation, and influence diversity through a cascade effect (POULIN, 2007). The occurrence and distribution of parasites in host populations depend on several factors that include host and parasite attributes, such as phylogenetic relationships, host behavior, susceptibility to parasites (BROUAT et al, 2007;WOLINSKA & KING, 2009), as well as characteristics of the environment such as seasonality and habitat (WOLINSKA & KING, 2009;SIMÕES et al, 2010;CASTRO et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Other studies have found similar results for C . tentaculata (Müller, 2005; Castro et al ., 2017; Costa-Neto et al ., 2019; Cirino et al ., 2020).…”
Section: Discussionmentioning
confidence: 99%